World Workshop on Oral Medicine VII: Targeting the oral microbiome Part 2: Current knowledge on malignant and potentially malignant oral disorders. (29th May 2019) - Robledo‐Sierra, Jairo; Ben‐Amy, Dalit Porat; Varoni, Elena; Bavarian, Roxanne; Simonsen, Janne L.; Paster, Bruce J.; Wade, William G.; Kerr, Ross; Peterson, Douglas E.; Frandsen Lau, Ellen
Abstract: Objective: The World Workshop on Oral Medicine VII chose the oral microbiome as a focus area. Part 1 presents the methodological state of the science for oral microbiome studies. Part 2 was guided by the question: What is currently known about the microbiome associated with oral squamous cell carcinoma and potentially malignant disorders of the oral mucosa? Materials and Methods: A scoping review methodology was followed to identify and analyse relevant studies on the composition and potential functions of the oral microbiota using high‐throughput sequencing techniques. The authors performed searches in PubMed and EMBASE. After removal of duplicates, a total of 239 potentially studies were identified. Results: Twenty‐three studies on oral squamous cell carcinoma, two on oral leukoplakia and four on oral lichen planus were included with substantial differences in diagnostic criteria, sample type, region sequenced and sequencing method utilised. The majority of studies focused on bacterial identification and recorded statistically significant differences in the oral microbiota associated with health and disease. However, even when comparing studies of similar methodology, the microbial differences between health and disease varied considerably. No consensus on the composition of the microbiomes associated with these conditions on genus and species level could be obtained. Six studies on oral squamous cell carcinoma had included in silico predicted microbial functions (genes and/or pathways) and found some similarities between the studies. Conclusions: Attempts to reveal the microbiome associated with oral mucosal diseases are still in its infancy, and the studies demonstrate significant clinical and methodological heterogeneity across disease categories. The immense richness and diversity of the microbiota clearly illustrate that there is a need for additional methodologically comparable studies utilising deep sequencing approaches in significant cohorts of subjects together with functional analyses. Our hope is that following the recipe as outlined in our preceding companion paper, that is Part 1, will enhance achieving this in the future and elucidate the role of the oral microbiome in oral squamous cell carcinoma and potentially malignant disorders of the oral mucosa.